2017
DOI: 10.5603/ait.a2017.0074
|View full text |Cite
|
Sign up to set email alerts
|

The role of point-of-care ultrasound in intra-abdominal hypertension management

Abstract: POCUS is a powerful systematic ultrasound technique that can be used as an adjuvant in intra-abdominal hypertension management. It has the potential to be used in both diagnosis and treatment during the course of IAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 11 publications
0
15
0
5
Order By: Relevance
“…Abdominal POCUS is widely used as a clinical tool for the management and diagnosis of patients with abdominal pathology [144][145][146][147][148]. Evaluation of free fluid is particularly useful when sudden clinical deterioration and hypotension occur and may provide insight into the ongoing pathophysiologic process [149,150] A renal ultrasound is useful to easily detect the presence of hydronephrosis even by novices [152][153][154]. Urinary retention can be evaluated by POCUS assessing postvoid residual volumes.…”
Section: Pocus-guided Technique Is Helpful Formentioning
confidence: 99%
“…Abdominal POCUS is widely used as a clinical tool for the management and diagnosis of patients with abdominal pathology [144][145][146][147][148]. Evaluation of free fluid is particularly useful when sudden clinical deterioration and hypotension occur and may provide insight into the ongoing pathophysiologic process [149,150] A renal ultrasound is useful to easily detect the presence of hydronephrosis even by novices [152][153][154]. Urinary retention can be evaluated by POCUS assessing postvoid residual volumes.…”
Section: Pocus-guided Technique Is Helpful Formentioning
confidence: 99%
“…Despite the fact that there are no existing predictive factors for IAH diagnosis, except for the risk factors, new technologies are already being used in the management of IAH. Recently, a study demonstrated the usefulness of bedside ultrasound for the management of critically ill patients with elevated IAP [8]. Accordingly, we believe that soon new studies will demonstrate clinical, laboratory and respiratory parameters as possible predictors of IAH, which in view of the observed differences among the admission SOFA scores of patients who developed ACS would possibly be used in addition to other parameters.…”
Section: Discussionmentioning
confidence: 98%
“…They concluded that IAH simulation was associated with decreased inferior vena cava cross-section area and an increased resistive index in renal arteries [29]. Pereira et al (2017) reporting on a group of fifty critically ill patients who developed IAH, showed that the point of care ultrasound (POCUS) proved to be extremely useful in evaluation of bowel activity, identification of large intestinal contents, the identification of patients who would benefit from bowel evacuation as an adjuvant to lower IAP and the diagnosis of moderate to large amounts of free intra-abdominal fluid [30]. Echocardiography can detect indirect but non-specific signs of ACS, decreased preload as well as dysfunctions of systolic and diastolic ventricular functions [31].…”
Section: Diagnosismentioning
confidence: 99%